Aktivitas Kombinasi Ekstrak Etanol Daun Sirsak (Annona muricata L.) Dan Daun Pegagan (Centella asiatica L.Urb) Terhadap Kelarutan Kalsium Batu Ginjal Secara In Vitro: Activitiy of Ethanol Extract Combination Between Soursop (Annona muricata L.) Leaves and Gotu Kola (Centella asiatica L.Urb ) Leaves on The Solubility of Kidney Stone Calcium In Vitro - Ni Wayan Swintari; Yuliet Yuliet; Khilda Khaerati (Universitas Tadulako, 2017)
Soursop (Annona muricata L.) and gotu kola (Centella asiatica L.Urb) is a plant that can be used as a laxative medicine kidney stones. This is because of the content of bioactive compounds including flavonoids, especially the leaf section. The use of a combination of soursop leaf extract and gotu kola can improve their effectiveness in order to remove calcium kidney stones. Therefore, this study aims to determine the activity and to determine dose combination soursop leaf ethanol extract (SS) and gotu kola leaf (GK) which is effective for dissolving potassium kidney stones. Extracts prepared by maceration method using ethanol 96% then subsequently tested phytochemical screening and thin layer chromatography profiles on each extract. Results chromatogram showed the extract containing flavonoids. Testing the activity of the combination of soursop and gotu kola extract performed using seven treatments, combination 1 (SS 1% + GK 7.5% ), a combination of 2 (SS 0.5% + GK 3.75%), the combination of 3 (SS 0, 25% + GK 1.875%), single soursop leaf extract (1%), single gotu kola extract (7.5%), negative control (aquadest) and positive control (Batugin elixir). Kidney stones are then put as much as 100 mg in each treatment and incubated for 6 hours (37 ℃). Results filtrate then didestruksi and dissolved calcium levels measured using Atomic Absorption Spectrophotometer. The results showed the combination soursop leaf ethanol extract and gotu kola leaf extract with a combination of 2 (SS 0.5% + GK 3.75%) is an effective combination of the ability to dissolve calcium kidney stones in vitro.